2021
DOI: 10.1186/s12958-021-00743-y
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin prevents primordial follicle loss via suppression of PI3K/Akt/Foxo3a pathway activation in cyclophosphamide-treated mice

Abstract: Background Chemotherapy improves the survival rates of patients with various cancers but often causes some adverse effects, including ovarian damage, characterised by a decrease in primordial follicle stockpiles. Recent studies have revealed that chemotherapy may stimulate the PI3K signalling pathway, thereby resulting in accelerated primordial follicle activation and a decreased ovarian reserve. Quercetin is an inhibitor of the PI3K pathway; however, its protective effects against chemotherapy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…Studies have also indicated that the ‘burnout’ effect could induce a reduction in primordial follicles following the activation and growth initiation of primordial follicles, as determined by the changing pattern of follicle numbers and TUNEL-negative primordial follicles even at 4 h/12 h/24 h and 3/7 days post-CTX exposure [ 10 , 14 , 25 ]. Despite the lack of direct evidence, numerous researchers have admitted the rationality of both theories and proposed a mechanism by which oocytes abandon their follicular quiescence to initiate DNA damage signaling pathways resulting in oocyte apoptosis [ 10 , 25 , 26 , 27 ]. Consistent with previous studies [ 10 , 14 ], we did not observe primordial follicle apoptosis on day 7 after CTX exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also indicated that the ‘burnout’ effect could induce a reduction in primordial follicles following the activation and growth initiation of primordial follicles, as determined by the changing pattern of follicle numbers and TUNEL-negative primordial follicles even at 4 h/12 h/24 h and 3/7 days post-CTX exposure [ 10 , 14 , 25 ]. Despite the lack of direct evidence, numerous researchers have admitted the rationality of both theories and proposed a mechanism by which oocytes abandon their follicular quiescence to initiate DNA damage signaling pathways resulting in oocyte apoptosis [ 10 , 25 , 26 , 27 ]. Consistent with previous studies [ 10 , 14 ], we did not observe primordial follicle apoptosis on day 7 after CTX exposure.…”
Section: Discussionmentioning
confidence: 99%
“…29 Li et al found that quercetin can prevent the loss of primordial follicles in mice by inhibiting the activation of the PI3K/Akt/FOXO3a pathway. 30 However, whether quercetin can inhibit ovarian oxidative stress and improve the ovarian microenvironment through the PI3K/Akt/FoxO3a signalling pathway has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Himani found that quercetin can reduce apoptosis by inhibiting Akt/PKB phosphorylation, reducing mitochondrial cystic release and downregulating Cu–Zn peroxidase dismutase to inhibit the ROS reaction 29 . Li et al found that quercetin can prevent the loss of primordial follicles in mice by inhibiting the activation of the PI3K/Akt/FOXO3a pathway 30 . However, whether quercetin can inhibit ovarian oxidative stress and improve the ovarian microenvironment through the PI3K/Akt/FoxO3a signalling pathway has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al found that exosomes from stem cells can enhance the expression of PI3K/Akt pathway, increase the proliferation rate of granulosa cells, and improve ovarian function in a POF mouse model (31). Li et al (32) found that quercetin attenuated cyclophosphamide-induced follicle loss by preventing the phosphorylation of PI3K/Akt/Foxo3 pathway members and maintaining the anti-Müllerian hormone level through reduced apoptosis in growing follicles (32). These findings imply that the PI3K/PTEN/Akt/Foxo3 cascade in oocytes is essential for the activation of primordial follicles (10).…”
Section: Pi K/pten/akt/foxo Pathwaymentioning
confidence: 99%